Aryne insertion reactions leading to bioactive fused quinazolinones: diastereoselective total synthesis of cruciferane - Vaidya, Sagar D.; N. P. Argade (Organic Letters, 2013)
Insertion reactions of an in situ generated arynes to a variety of suitably substituted 1,3-quinazolin-4-ones have been demonstrated for a new efficient one-step approach to a diverse range of fused quinazolinone architectures. The present protocol has been effectively utilized to accomplish the concise total synthesis of recently isolated bioactive natural products tryptanthrin, phaitanthrins A-C, and cruciferane.

Biomimetic synthesis of phaitanthrin e involving a fragmentation of sp(3) carbon-carbon bond: synthesis and rearrangement of phaitanthrin D to phaitanthrin E - Vaidya, Sagar D.; N. P. Argade (Organic Letters, 2015)
A biogenetic type total synthesis of alkaloids phaitanthrin D and phaitanthrin E has been described. The Csp(3)-Csp(3) bond cleavage with the release of several heteroatoms bearing unexpected leaving groups in intramolecular substitution reactions on an iminium double bond in the quinazolinones has been demonstrated using HMDS/ZnCl2 or NaHMDS. The mechanistic aspects have been supported by isolation and characterization of appropriate intermediates.

Synthesis of (-)-phaitanthrin D and (+)-dihydropyrroloindoloquinazolinone - Vaidya, Sagar D.; N. P. Argade (Synthesis-Stuttgart, 2016)
The synthesis of (-)-phaitanthrin D and (+)-dihydropyrroloindoloquinazolinone are reported starting from the corresponding especially designed enantiomerically pure pivotal anthranilamide based building blocks using HMDS/ZnCl2 and NaHMDS.

Rearrangement of imine double bond in activated quinazolinones: synthesis of phaitanthrin E - Vaidya, Sagar D.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2017)
Wolff-Kishner reduction of tryptanthrin to indoloquinazolinone followed by lithium diisorpropylamide induced acylation of the active methylene group with methyl chloroformate directly furnishes the phaitanthrin E in very good yield. Similar acylations of indoloquinazolinone have also been performed with four different acyl chlorides. In all examples, facile rearrangement of imine double bond from quinazolinone to indole moiety to form the corresponding alpha,beta-unsaturated carbonyl system is observed.